Analisis Pengambilan Keputusan Penggunaan Kendaraan Operasional Tambang dengan Metode Bow Tie Analysis dan Analitycal Hierarchy Process (AHP) - Fatimah Dewi Firdausy; Tranggono Tranggono; Rizky Novita Sari (Universitas Batanghari Jambi, 2026)
The aim of this research is to determine the best mode of transportation between conventional fueled mining operational vehicles and electric fueled mining operational vehicles based on risk analysis. This research was conducted using the Bow Tie Analysis method which is used to identify, evaluate and manage risks by showing the cause and effect relationship of a risk and appropriate mitigation measures in conventional fueled mining operational vehicles and electric fueled mining operational vehicles and the Analytic Hierarchy Process ( AHP) is used to be able to choose the best mode and minimize problems or risks that can occur in company activities and methods. The results of calculations at all levels using expert choice 11 software showed that the final calculation results for selecting the use of selected mining operational vehicles obtained the highest priority vector ranking, namely alternative electric mining operational vehicles with a percentage of 55.0%. Risk of Discomfort to the Community is the type of risk with the highest ranking with a percentage of 42.7%, meaning that the risk of discomfort to the community is the biggest consideration for PT X